Objective nutritional indices as an independent predictor of functional outcome after endovascular therapy for acute ischemic stroke: a cohort study in a Chinese population - Gao, Weiwei; Yu, Lingfeng; Zhang, Yifen; Jin, Shouyue; Chen, Zhongjie; Chen, Xingyu; Cai, Lijuan; Zhu, Renjing (Frontiers in Nutrition, 2025)
ObjectiveTo investigate the associations between three nutritional indices—Prognostic Nutritional Index (PNI), Controlling Nutritional Status (CONUT) score, and Hemoglobin-Albumin-Lymphocyte-Platelet (HALP) score—and 90-day functional outcomes in patients with large vessel occlusion acute ischemic stroke (LVO-AIS) who underwent endovascular therapy (EVT).MethodsIn this retrospective cohort study, we consecutively enrolled 409 LVO-AIS patients who received EVT at a comprehensive stroke center between January 2019 and December 2024. The primary endpoint was poor functional outcome, defined as a modified Rankin Scale (mRS) score of 3–6 at 90 days. Associations between nutritional indices and functional outcomes were analyzed using multivariable logistic regression models with stepwise adjustment. Restricted cubic spline (RCS) analysis was performed to explore potential non-linear relationships. Subgroup analyses with interaction tests assessed the consistency of these associations across demographic and clinical subgroups.ResultsAt 90-day follow-up, 261 patients (63.8%) had poor functional outcomes. The prevalence of malnutrition risk varied substantially between nutritional indices: PNI identified 15.9% of patients at risk, whereas the CONUT scoring system classified 81.9% of patients as having some degree of malnutrition risk. After comprehensive adjustment for confounders, each one-unit increase in PNI was associated with a 6% reduction in the risk of poor outcomes (adjusted OR = 0.94, 95% CI: 0.89–0.99, p = 0.026), while each one-unit increase in HALP score was associated with a 3% reduction (adjusted OR = 0.97, 95% CI: 0.96–0.99, p = 0.001). RCS analysis revealed a significant non-linear relationship between HALP score and functional outcomes (P-non-linear = 0.021), characterized by a steep risk reduction as scores increased at lower values, followed by a plateau effect. Subgroup analyses demonstrated consistent associations between nutritional indices and outcomes across various demographic and clinical characteristics, with no significant interaction effects observed.ConclusionPrognostic Nutritional Index and HALP scores serve as independent predictors of poor 90-day functional outcomes in LVO-AIS patients treated with EVT. The significant non-linear relationship observed between HALP score and functional outcomes suggests that interventions targeting patients with moderate to severe malnutrition risk may yield greater clinical benefits.